(untitled) (Iranian Journal of Kidney Diseases, 2014)
Introduction. Patients with chronic kidney disease (CKD) face with uremic toxins. Lactulose could reduce serum urea and creatinine levels and have some effects on lipid profile and bone minerals. The aim of this study was to evaluate effect of lactulose on serum levels of biochemical products in patients with CKD. Materials and Methods. In this prospective study, 40 patients with stages 3 and 4 of CKD (52.5% men; mean age, 57.5 ± 12.5 years) were evaluated. All patients received lactulose, 30 mL, 3 times per day for 2 months. Blood samples from all participants were collected before and at the end of intervention to examine changes in biochemical parameters, including sodium, potassium, hemoglobin, urea, creatinine, uric acid, leukocyte and platelets count, β2-microglobin, and intact parathyroid hormone. Results. Lactulose significantly decreased urea levels from 70.35 ± 28.00 mg/dL to 64.50 ± 23.51 mg/dL (P = .04), creatinine levels from 4.04 ± 1.78 mg/dL to 3.45 ± 1.39 mg/dL (P < .001), uric acid levels from 7.31 ± 1.49 mg/dL to 6.71 ± 1.42 mg/dL (P < .001), and β2-microglobin levels from 3.25 ± 0.44 mg/L to 3.08 ± 0.33 mg/L (P = .001). The decrease in serum electrolytes, lipid profile, and intact parathyroid hormone levels were not significant. Conclusions. Lactulose administration in CKD patients could decrease levels of various deleterious elements, especially nitrogen products, and its daily use can be recommended in these patients.